Perinatal regionalization of resources in Latin America Feasibility of regionalization by levels of care; Implementation of the first referral level. - Pacheco Romero, José (2015)
The sociodemographic and economic conditions in Latin America are characterized by poor and unsatisfactory sanitary facilities. Under optimal circumstances, 990 out of 1000 pregnancies that reach the seventh month of pregnancy conclude with a newborn and mother healthy. Meanwhile, in developing countries, one in 50 women die due to pregnancy, childbirth and postpartum, compared to one in 2,700 in developed countries. Latin America has taken with the world's nations committed to Health for All by the year 20008 and the reduction of maternal and infant mortality. But our region see that this goal is still distant and maternal and perinatal morbidity and mortality, useful indicators of the health status of a country, improve very slowly.